PERANAN DAN KEPENTINGAN STAKEHOLDER DALAM PENGELOLAAN WILAYAH PESISIR (Studi Kasus di Desa Sidodadi Kabupaten Lampung Selatan) - Budi Sulistio, Eko (Indonesian Journal of Socio Economics)
The main objective of this research is to describe more deeply about the process of the coastal zone management and the various stakeholder involvement in the coastal zone in Sidodadi Village, South Lampung District. This research uses qualitative approach, which the process of data gathering is conducted by means of interview, observation and documentation. The data is analyzed using interactive analysis model that consisted of data reduction, data display and verification. The study shows that the process of coastal zone management in Sidodadi Village is distinguised into two sectors, i.e. the environmental management and the economic and socio-culture managements. The environmental management in coastal zone has conducted according the sequence of planning, implementing, maintaining and controlling. While, the economic and socio-culture management in coastal zone is not conducted yet as well as the environmental management. The various stakeholders in coastal zone in Sidodadi Village are: (1) The Government of South Lampung District represented by The Agency of Environmental and Land UseÂ  (BTRLH), Agency of Marine and Fisheries (DPK) and Agency of Culture, Art and Tourism (BPSB), (2) Nongovernment Organization (LSM Watala), (3) Private Sector/ bussinessman and (4) Sidodadi Village native communities. Lack of support from stakeholders, especially from local government, can decrease the local communities enthusiast to participate in the coastal zone management.